Je t’aime pour toi, pas pour ta nationalité ! De la politisation du désir entre tolérance et préférence à Mascate, Sultanat d’Oman - Marion Breteau (Arabian Humanities)
After coming to power in 1970, Sultan Qaboos bin Said has been striving to promote equal rights among Omanis, based on national preference. This political discourse also draws its legitimacy from religion; based on an ideal of tolerance born of the state religion, Ibadism, to the point of pervading individual representations when choosing a spouse. The foundations of national identity question the notion of modernity, perceived as a process of transformation in marriage, where individual choice takes precedence over family preferences. This article endeavors to observe how the politicization of love and matrimonial alliance is taking place, based on ideals of equality and tolerance, as opposed to preferences and exclusion.